PENGEMBANGAN PERANGKAT PENILAIAN KINERJA DAN SIKAP PADA PRAKTIKUM TITRIMETRI DAN GRAVIMETRI SMK-SMTI MAKASSAR - Widya Dwi Anggraini (Program Pasca Sarjana UNM, 2017)
This research aims to produce performance assessment and attitudes tools on titrimetric and gravimetric Laboratory which valid, reliable, and practical. Validity based on judgment of expert on performance assessment tools and attitudes that are developed, reliability obtained from Alpha Cronbach coefficient values based SPSS, and practicality is obtained from the value of teachers' questionnaire responses and performance assessment tools developed attitude. This development step consists of five steps: (1) preliminary investigation with excute identify information, analyze information, to limit the problem, and plan continuation activity; (2) design with excute design performance and attitude assessment in form matriks performance and attitude assessment; (3) realization or construction with excute to make first draft; (4) test, evaluation, and revision with excute to judgement of ekspert; and (5) implementation with excute to trials carried out. The instrument which used are classifier for paper validation for measure validity and reability as well as teachers' questionnaire responses for measure practicality. The results showed that the performance assessment and practical attitude on titrimetric and gravimetric meet the criteria of valid, reliable, and practical. Mean valid, reliable, and practical in sequence are 0,965; 0,807; and 64,87 assessments is based on both validator and based on trials carried out at the Department of Industrial Chemistry students SMK-SMTI Makassar.